The role of transparency in influencing revenue generation, public participation, and allocation efficiency in Ghana - Oti-Akenteng, Ernest; Ocansey, Evans O. N. D.; Asamoah, Felix Oppong (International journal of economic perspectives, 2025)
Transparency in governance plays a crucial role in promoting accountability, efficiency, and citizen engagement. However, its impact on revenue generation, public participation, and allocation efficiency remains underexplored in the Ghanaian context. This study examines the mediating role of transparency in shaping these governance outcomes. The study aims to assess how transparency influences revenue generation, public participation, and allocation efficiency in Ghana. It also explores the extent to which institutional quality, economic development, and political stability interact with transparency to shape governance outcomes. The study employs quantitative secondary data analysis spanning from 2010 to 2022, sourced from the World Bank, the Bank of Ghana, and international governance indices. The data is analyzed using descriptive statistics, correlation analysis, stationarity tests, and multiple regression models to establish the relationship between transparency and governance performance. The results reveal that transparency significantly enhances public participation while showing a positive but marginally insignificant effect on revenue generation. However, transparency alone does not significantly influence allocation efficiency without strong institutional and political frameworks. Economic development negatively affects both revenue generation and allocation efficiency, highlighting governance challenges in growing economies. The study recommends strengthening digital transparency initiatives, enhancing institutional quality, and integrating emerging technologies like AI-driven audits and blockchain-based public finance tracking. Additionally, policies should promote participatory governance to enhance citizen engagement while ensuring that transparency reforms are embedded in broader governance structures.